2008
DOI: 10.1016/j.juro.2008.08.051
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Flexible Ureteroscopic Lithotripsy: The Children's Hospital of Philadelphia Experience

Abstract: Pediatric ureteroscopy is a safe and efficacious modality in the treatment of all upper urinary tract calculi, including lower pole calculi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
1
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(66 citation statements)
references
References 17 publications
1
58
1
6
Order By: Relevance
“…They found that success rates were correlated with stone dimension, where need for additional procedure was correlated with both stone dimension and patient age. In a series of 167 patients with a mean age of 62.4 months, Kim et al [33] reported a SFR of 100% and 97% in stones smaller and bigger than 10 mm, respectively, without any intraoperative and postoperative complications. Insertion of a stent was required in 57% of the patients in whom an access was not achieved.…”
Section: Rirs In Pediatric Patientsmentioning
confidence: 98%
“…They found that success rates were correlated with stone dimension, where need for additional procedure was correlated with both stone dimension and patient age. In a series of 167 patients with a mean age of 62.4 months, Kim et al [33] reported a SFR of 100% and 97% in stones smaller and bigger than 10 mm, respectively, without any intraoperative and postoperative complications. Insertion of a stent was required in 57% of the patients in whom an access was not achieved.…”
Section: Rirs In Pediatric Patientsmentioning
confidence: 98%
“…Kim et al also performed flexible ureteroscopy in children aged between 3 and 218 months (mean 62.4 months) with a stone burden 3-24 mm with an average of 1.3 stones per patient. 19 The procedure was performed without ureteric dilatation. However in 57% access could not be obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Taşları <10 mm olanlarının hepsinde, >10 mm olanlarının %97'sinde taşsızlık sağ-landı. Herhangi bir intra ve postoperatif komplikasyon izlenmedi 10 . Ünsal ve ark., 16 hastada RIRC etkinliğini araştırdı.…”
Section: Finansal Destekunclassified